Effect of selected marketing communication tools on student enrolment at private college : a study at KPTM Kota Bharu / Nur Ain Mohd Yusoff - Mohd Yusoff, Nur Ain (2012)
The aim of this study is to examine the effect of selection marketing communication tools on student enrolment at Kolej Poly-Tech MARA Kota Bharu. There are four that have been studied, which are: college appearance, advertising, public relation and direct marketing. In collecting data, the researcher used both secondary and primary data. The questionnaire had been used in order to get feedback from the student since the researcher used student as the respondent. Researcher had distributed randomly to 115 students at KPTM. Out of 100, about 80 questionnaires back. The data collected was tested on its frequency analysis. Further analysis has been done by using reliability analysis. Correlation was used to test the hypothesis. The findings of this study show that all independent variables which are college appearance, advertising, public relation and direct marketing have relationship with student enrolment at KPTM. Out of four independent variables, all the variables have influences student to enrol at KPTM. From the result obtained in this study, researcher suggests some recommendation that can help KPTM to improve and increase their student enrolment